Racial Identity Profiles Among Suicidal Black Women: A Replication and Extension Study. (October 2020) - Mekawi, Yara; Lewis, Ciera B.; Watson-Singleton, Natalie N.; Jatta, Isatou F.; Ander, llana; Lamis, Dorian; Dunn, Sarah E.; Kaslow, Nadine J.
Despite increasing rates of suicidality among African American women, relatively little is known about culturally-specific factors relevant to their suicidality. Thus, our objectives were to: (1) determine whether previously-identified racial identity profiles replicated in a clinical sample of African American women and (2) examine whether profiles differed on suicidal ideation, hopelessness, and depressive symptoms. In a sample of 198 low-income, African American women ( M age  = 36), latent profile analysis supported a 5-class solution: Undifferentiated (average on all subscales), Detached (lower than the average on most subscales), Afrocentric (low public regard, high nationalism), Multiculturalist (high public regard, private regard, centrality), and Alienated (markedly lower than average on all subscales). Subgroups with higher racial group identification and more positive feelings about being African American endorsed less suicidal ideation and hopelessness than other subgroups. This study characterizes patterns of racial identity among a clinical sample and offers insights into how subgroups of individuals with different combinations of racial identity may be more likely to experience suicidality.